2021
DOI: 10.1002/acr.24787
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Blood Flow Restriction Training in Patients With Knee Osteoarthritis: A Systematic Review and Meta‐Analysis

Abstract: Objective To evaluate the efficacy and safety of blood flow restriction training (BFRT) in the treatment of patients with knee osteoarthritis (OA). Method Seven electronic databases were searched to identify trials comparing BFRT and conventional resistance training in a population with knee OA. Studies were selected according to the inclusion and exclusion criteria. Standardized mean differences (SMDs) or risk ratios (RRs) with 95% confidence intervals (95% CIs) were calculated to compare outcome measures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
3
3
0
Order By: Relevance
“…In addition to physical functions, we also focused on the quality of life, but our summary results indicate that there was no signi cant improvement in the BFRT group as opposed to the control group. This is consistent with previous meta-analysis results [30].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition to physical functions, we also focused on the quality of life, but our summary results indicate that there was no signi cant improvement in the BFRT group as opposed to the control group. This is consistent with previous meta-analysis results [30].…”
Section: Discussionsupporting
confidence: 94%
“…However, two studies did not nd a marked improvement compared with the control group. These ndings align with those of previous meta-analyses involving older individuals [30,31].…”
Section: Discussionsupporting
confidence: 91%
“…In a study conducted in patients with sporadic inclusion body myositis, a disease is also associated with decreased muscle strength, as is the case with neurological disorders [ 47 ], the training protocol with BFR did not improve objective physical function but it had a preventive (retaining effect) effect on the leg muscle strength [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another recent meta-analysis including nine studies on various knee disorders found that muscle strength increases were comparably superior for LL-BFRT, and HL-RT compared to LL-RT, with pain improvement superior for LL-BFRT compared to LL-RT and HL-RT [142]. Systematic reviews have also found benefit of LL-BFRT for increasing muscle strength and function in clinical patients during rehabilitation for pre-and post-operative anterior cruciate ligament (ACL) reconstruction [143][144][145][146][147], knee surgery [148], osteoarthritis [149,150], various knee conditions [151][152][153][154], muscular atrophy [155], sarcopenia [156], and elderly patients at risk for various musculoskeletal conditions [113][114][115][116]. The safety of BFRT in musculoskeletal rehabilitation has also been assessed as comparable to standard exercise therapy, with a systematic review of 19 studies finding that the likelihood of adverse events is not increased with BFRT, despite suggestions of potential safety concerns [88].…”
Section: Bfrt Musculoskeletal Rehabilitation Outcomesmentioning
confidence: 99%